The Urinary Hormonal State of Cats Associated With Social Interaction With Humans - Nagasawa, Takumi; Ohta, Mitsuaki; Uchiyama, Hidehiko (Frontiers in Veterinary Science, 2021)
Research to assess the relationship between cats and humans is in a nascent stage. Some studies have assessed the stress status in cats using physiological indicators, such as the cortisol hormone, but have not focused on the social interaction with humans. Moreover, the role of oxytocin secretion in the relationship between cats and humans remains unclear. In this study, we determined the possibility of quantifying the urinary concentration of oxytocin in cats and assessed the effects of social contact with humans on the levels of urinary oxytocin and cortisol. Four cats were subjected to two conditions, namely social (control) and non-social (no social contact with humans) conditions. The levels of cortisol and oxytocin in urine samples from cats in both conditions were determined using enzyme-linked immunosorbent assays. The urinary concentrations of cortisol and oxytocin under the non-social condition were significantly higher than those under the social condition. In addition, the concentration of oxytocin significantly correlated with that of cortisol in cats under the non-social condition. In this study, it was possible to quantify the concentration of oxytocin in cats’ urine, and the obtained results suggest that cats recognize the social interaction with humans as important. This information might contribute to the establishment of an assessment method for the welfare of cats and might help in clarifying the relationship between cats and humans.